Rasionalitas Dan Modernisasi Ekonomi Politik Di Aras Civil Society - Azizah, Nurul (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2014)
The following article depicts the impact of the implementation of modernization of rural economic-politic (system) in the new order era towards its natural resources, which had put them, the peasant community, in disadvantaged position, especially those belong to the poor group of civil society, since they prioritized more on the preservation of the foreign investments which at the end led to the issue of the maintaining the status quo of the new order regime and their political interests; as well as illustration of the rural renewal strategy.